2008
DOI: 10.1044/1058-0360(2008/005)
|View full text |Cite
|
Sign up to set email alerts
|

Preparation in Augmentative and Alternative Communication: An Update for Speech-Language Pathology Training

Abstract: Academic preparation in AAC, while varying across academic programs, has in general increased over the past decade. Data also suggested a continuing critical need for more academic and clinical preparation in this area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 13 publications
2
33
0
4
Order By: Relevance
“…Similar results have been reported from surveys of SLPs in egypt (Wormnaes & Malek, 2004) and New zealand (Sutherland, Gillon, & yoder, 2005). Lack of pre-professional training beyond the basic AAC skill set may adversely impact the quality of service provided to people with complex communication needs (Beukelman & Cumley, 1992;Costigan & Light, 2010;Lindsay, 2010;Marvin et al, 2003;Ratcliff, Koul, & Lloyd, 2008).…”
Section: Introductionsupporting
confidence: 72%
“…Similar results have been reported from surveys of SLPs in egypt (Wormnaes & Malek, 2004) and New zealand (Sutherland, Gillon, & yoder, 2005). Lack of pre-professional training beyond the basic AAC skill set may adversely impact the quality of service provided to people with complex communication needs (Beukelman & Cumley, 1992;Costigan & Light, 2010;Lindsay, 2010;Marvin et al, 2003;Ratcliff, Koul, & Lloyd, 2008).…”
Section: Introductionsupporting
confidence: 72%
“…Acquiring this competence involves indepth educational programs that address both medical and technical requirements. Early studies by Koul and Lloyd (1994), Ratcliff and Beukelman (1995), and Ratcliff, Koul, and Lloyd (2008) revealed that between 62% and 73% of students with degrees in speech-language pathology had taken courses specific to AAC. Among the 73% respondents from Ratcliff et al's study (2008), 80% indicated that AAC training was incorporated within a number of courses.…”
Section: Respondents' Exposure and Training In Aacmentioning
confidence: 98%
“…Since 1990, the number of pre-professional programs in colleges and universities designed to prepare AAC-related personnel has increased considerably. Ratcliff, Koul, and Lloyd (2008) conducted a 2006 survey of 290 individuals associated with speech-language pathology pre-professional preparation programs across the United States. They reported the following: Of the 168 surveys that were returned, 68% of the respondents reported that the AAC courses they took were taught via on-site lectures with or without Internet-based supplemental information; 11% said AAC coursework was offered via the web; 52% indicated that an AAC course was required, 48% indicated that courses were electives; and 80% reported that AAC content had been fused into other courses.…”
Section: Looking Toward the Futurementioning
confidence: 99%